Measuring the user experience : collecting, analyzing, and presenting usability metrics - Tullis, Tom (Thomas) (Morgan Kauffmann/Elsevier, 2013)
This book provides the quantitative analysis training that UX and web professionals need to collect a broader range of data about the user experience. It covers emotional engagement, personas, keystroke analysis, and net promoter score, and examines how new technologies coming from neuro-marketing and online market research can refine user experience measurement, helping usability and user experience practitioners make business cases to stakeholders.